"Think globally, act locally": A glocal approach to the development of social media literacy. (January 2021) - Manca, Stefania; Bocconi, Stefania; Gleason, Benjamin
Abstract: Despite the documented number of studies that investigate social media in teaching and learning settings, the topic of social media literacy is still an under-researched area. This study adopts the theoretical lens of New Literacy studies to suggest a combined perspective for investigating social media literacies. This perspective considers both social media skills that are transversal across different social media (global skills), and those that pertain to a specific social media platform (local skills). It examines practices that are decontextualized (literacy as something to be acquired), and those that are situated and context-dependent (literacy through participation). To map current research on social media skills, a systematic literature review was conducted. Analysis of 54 publications was carried out following the UNESCO DLGF framework for digital literacy competencies, and also using a critical lens based on four metaphors whereby, for learning purposes, social media are seen as a tool, as a process, as collaboration, and as participation . The results show that most of the studies consider global social media skills, while only a few examine skills sets specific to a particular social media platform. In addition, most of the identified skills concern decontextualized practices, with very few studies emphasizing the importance of fostering situated social media practices. We conclude that there is a need for more expansive theoretical elaboration in the field, and provide a number of recommendations for investigating, understanding, and designing educational curricula and activities that support the development of social media literacy. Highlights: Social media literacy is still an under-researched area. Global and local social media skills are considered in social media literacy. Social media practices are decontextualized or situated and context-dependent. 54 articles on social media literacy are systematically reviewed. There is a need for more expansive theoretical elaboration in the field.